Intrinsic motivation among Arabic language students - Yusri, Ghazali; Yusoff, Muhammad Saiful Anuar; Sardi, Janudin; Abdul Majid, Muhammad Arsyad; Muhammad Isa, Abdul Azim; Puasa, Bashasunnahar (Universiti Teknologi MARA, Kedah, 2025)
Intrinsic motivation is one of the most important types of motivation in the learning process. Individuals with intrinsic motivation tend to engage in activities for their personal fulfillment, curiosity and self satisfaction. This study aimed to investigate students’ intrinsic motivation in learning oral Arabic. It combined both methods of quantitative and qualitative study using a questionnaire adapted from The Motivated Strategies for Learning Questionnaire (MSLQ) and interviews. The stratified random sampling technique was used for quantitative data involving 455 samples while for qualitative data, 13 interviews with students were engaged. The selection of students took into consideration their prior experience in learning Arabic and the faculties they belonged to. The study found that the intrinsic motivation among students was high. It was also found that there were statistically significant differences in this motivation among some groups of students with different prior experience. This study had some classroom implications. It suggested that students in UiTM should be separated according to their prior experience. Otherwise, some additional Arabic classes should be carried out to less experienced students before they enroll in actual Arabic classrooms in order to narrow the gaps between them. Another alternative is to initiate activities involving students of mixed experience in one group in order to create a collaborative grouping environment and to bridge the motivation gaps between them.